Minority Savings and Loan Associations: Hypotheses and Tests - Bradford, William D. (Journal of Financial and Quantitative Analysis, 1978)
Many writers believe that minority-owned financial institutions can and should play an important role in aiding the economic development of minority communities. Indeed, economic theory describes a major role of financial institutions as gathering many relatively small deposits of households and other economic units, and combining these to support capital formation through lending for business and housing capital investment. The service which minority financial institutions can play may be magnified by the much-discussed inability of minority communities to obtain financing from nonminority financial institutions for business capital investment and–of more recent concern–for housing capital investment. The concept of pooling the savings of ghetto residents and putting the savings to work in financing the development of the inner city community may be sound in theory, but what does the empirical evidence indicate about its practical implementation?